Case study of the Home Energy Saving Scheme : a multidisciplinary approach - Byrne, Amiee Jennifer (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
The EU has set itself the objective of achieving 20% primary energy savings by 2020. Because of the relatively recent move towards sustainability, there is a limited understanding of how effective related policies and actions have been. This in turn stymies the development and impact of such policies. To this end, this thesis examines the case study of the Irish government's national grant scheme to encourage energy efficiency retrofit in private housing. That is the Home Energy Saving (HES) Scheme, later rebranded the Better Energy; Homes (BEH) scheme. The methodology design draws from the disciplines of structural engineering, thermal engineering and human geography.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin